Design and Development of an Indigenous Drum Dryer for Preheating of Plastic Scrap. Issue 1 (December 2020) - Alam, Parvez; Dwivedi, Vijay Kumar; Islam, Anas; Sharma, Rohit
Abstract: In this experiment an indigenous plastic scrap preheating machine has been developed that preheats the plastic scrap very economically and may be used at small scale industries, as such types of industries largely uses sun drying method for heating the plastic scrap. The limitation of such method is that the time taken to heat the scrap is quite large and also there remains porosities inside the plastic scrap, these porosities create voids in these scraps that reduce the strength of the final manufactured plastic item in operations like injection mouldings.